In Vitro and In Vivo Evaluation of Metformin Hydrochloride Hydrogels Developed with Experimental Design in the Treatment of Burns - Ozyilmaz, Emine Dilek; Celikkaya, Rojhat; Comoglu, Tansel; Ozakpinar, Hulda Rifat; Behzatoglu, Kemal (Springer, 2023)
Burns alter the normal skin barrier and affect various host defense processes that help prevent infections. An ineffective repair process can lead to serious damage, such as the onset of an infection or skin loss, which can then harm the surrounding tissues and ultimately the entire organism. This study aims to prepare in situ gels containing metformin hydrochloride, a compound known for its wound healing properties. To achieve this, in situ gels were prepared using three different gelling agents (Poloxamer 407((R)), Carbopol 934((R)), and sodium carboxymethyl cellulose (Na-CMC)) and three different concentrations of metformin hydrochloride (4 mg/g, 6 mg/g, and 8 mg/g), which were optimized through experimental design. Metformin concentration and gelling agent type were independent variables, and the loaded amount and the percentage of metformin released after 150 min were chosen as dependent variables in the optimization process. After determining the optimum values of the dependent variables according to the ANOVA analysis results, in vivo studies were conducted with optimized hydrogel formulations. Two groups, each consisting of seven Wistar rats with a burn model, were treated with metformin-poloxamer 407((R)) gels at doses of 4 mg/g and 8 mg/g for 29 days. The results were then compared to untreated and placebo gel groups. Rats treated with in situ Poloxamer 407((R)) hydrogels containing metformin hydrochloride showed a significant reduction in the size of the burned area after 29 days of treatment. However, for a comprehensive understanding of the wound healing mechanism, further studies such as immuno-histochemical and cell culture studies are needed.
Keywords: burn wound healing; experimental design; in situ gel; in vivo tests; metformin hydrochloride